2019
DOI: 10.1002/pen.25234
|View full text |Cite
|
Sign up to set email alerts
|

Injection molding of delamination‐free ultra‐high‐molecular‐weight polyethylene

Abstract: When ultra‐high‐molecular‐weight polyethylene (UHMWPE) in powder form is injection molded, the so‐called delamination layering occurs near the skin of the parts. This layering defect hampers UHMWPE's superior wear resistance property and part surface quality. The delamination layer was caused by a combination of excessive shear stress near the part surface and high degree of molecular entanglement of UHMWPE. A mold insulation method that delays the rapid cooling of UHMWPE to reduce the shear stress and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Injection molded Neat UH and UHMWPE/HDPE blend samples had an obvious delamination defect. The delamination defect manifested during injection molding could be attributed to the excessive shear stress and poor “inter‐diffusion” among entangled UHMWPE chain bundles during the filling and packing stages 16 . The high shear stress at the interface of the frozen skin layer and molten core layer resulted in severe melt fracture, and hence hindered the diffusion and consolidation of the frozen and core layers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Injection molded Neat UH and UHMWPE/HDPE blend samples had an obvious delamination defect. The delamination defect manifested during injection molding could be attributed to the excessive shear stress and poor “inter‐diffusion” among entangled UHMWPE chain bundles during the filling and packing stages 16 . The high shear stress at the interface of the frozen skin layer and molten core layer resulted in severe melt fracture, and hence hindered the diffusion and consolidation of the frozen and core layers.…”
Section: Resultsmentioning
confidence: 99%
“…The delamination thickness decreased with increasing HDPE content. It was found in our previous work 16 that the delamination defect could be eliminated by applying either mold insulation or rapid heat cycle molding (RHCM) technology 31,32 to increase the mold wall temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to minimize metallic wear, ultra‐high‐molecular‐weight polyethylene (UHMWPE) is used as bushing. [ 3 ] However, the effect of wear particles still cannot be effectively eliminated. [ 4 ] Some studies have shown that polyether ether ketone (PEEK) has much higher wear resistance than UHMWPE.…”
Section: Introductionmentioning
confidence: 99%